Protective role of Nigella sativa oil on renal damage induced by acetaminophen in male rats - Hamad, Zena M. (The Iraqi Journal of Veterinary Medicine, 2017)
Acetaminophen also called paracetamol is commonly used as analgesic and antipyretic agent which in high doses causes liver and kidney damage in man and animals. Nigella sativa oil have antioxidant properties. Thirty adult male rats were used and randomly divided into three equal groups. Group (A) untreated and served as control group; Group (B) rats were orally intubated (by gavages needle) acetaminophen suspension (150mg/kg B.W). Group (C) rats were given orally acetaminophen suspension (150mg/kg) plus 1ml/kg B.W of Nigella sativa oil for 42 days in both treated group. Fasting blood samples were collected at 21 and 42 days of experiment to study the following parameters: Serum creatinine concentration and blood urea nitrogen concentration. The results revealed a significant increase of acetaminophen group in serum creatinine and blood urea nitrogen concentrations as compression with GA. Animals treated with Nigella sativa oil plus acetaminophen (C) showed a significant decline in serum creatinine and blood urea nitrogen concentrations. In conclusion, the acetaminophen was effective in induction of oxidative stress and change in some biological markers related to kidney disease. Also it seems that Nigella sativa oil exerts protective actions against the damaging effect of acetaminophen